Histamine and gut mucosal immune regulation. Issue 3 (29th November 2013) - Smolinska, S.; Jutel, M.; Crameri, R.; O'Mahony, L.
Abstract Histamine is a biogenic amine with extensive effects on many cell types, mediated by the activation of its four receptors (H1R–H4R). Distinct effects are dependent on receptor subtypes and their differential expression. Within the gastrointestinal tract, histamine is present at relatively high concentrations, particularly during inflammatory responses. In this review, we discuss the immunoregulatory influence of histamine on a number of gastrointestinal disorders, including food allergy, scombroid food poisoning, histamine intolerance, irritable bowel syndrome, and inflammatory bowel disease. It is clear that the effects of histamine on mucosal immune homeostasis are dependent on expression and activity of the four currently known histamine receptors; however, the relative protective or pathogenic effects of histamine on inflammatory processes within the gut are still poorly defined and require further investigation.